Rekayasa Mesin Perajang Tembakau Mole - Wahyu K Sugandi; Ahmad Thoriq; Asep Yusuf; Firdaus Firdaus (The University of Lampung, 2021)
Sukasari in Sumedang areas is one of the areas producing mole tobacco with the best quality with a production capacity of 1.2 tons.ha-1 once harvested. However, the tobacco chopping system has been still conventional which results in the inhibition of tobacco supply from producers (farmers) to consumers. The tool used was to use a knife to slice rolled tobacco with a chopping capacity of 35 kg per 2 worker per day. So the time was need to chopped 1.2 tons of tobacco in 35 days. Besides to long processing time, farmers often feels of back pain sick and right hand cramps, considering the average age of farmers have been above 50 years because the chopping process is carried out every day when the harvest season arrives. Therefore, a study need regarding the engginering design and technical analysis of tobacco chopper machines so that the chopping capacity can the production capacity of 1.2 tons.ha-1. The aims of study is to design a prototype tobacco chopper machine with a capacity of 140 kg.hour-1. This method used in this research is engineering design which is to carry out a design activity that is not routine, so that in it there is a new contribution, both in form and product. The result of the technical analysis of this tobacco chopper machine is that the chopping power is 0.59 HP, the dimensions of the chopper machine are 800 mm (length) x 757 mm (width) x 1000 mm (height) with the prime mover using a 1 HP electric motor. Actual capacity based on measurement is 66 kg/hour with 96.7% yield. Keywords: chopper machine, engine design, mole tobacco